Synthesis And Characterization Of Multi-Doped (Mg2+, Si4+ , Cu2+, Fe3+) Carbonated Hydroxyapatite Via Nanoemulsion Method - Ezekiel, Iliya (2018)
Synthesized hydroxyapatite (HA) with composition close to the mineral phase of the natural bone has been widely used for biomedical applications such as bone substitute, drug delivery and coating for implants. The goal of this study was to synthesize and characterise of multi-dope (Mg2+, Si4+, Cu2+, Fe3+) carbonated hydroxyapatite via nanoemulsion route to enhance its physical, mechanical and biological properties. The compositions were categorized into [nCO32-/nPO43-] molar ratio = 0.67 and 1.00 based on the carbonate content. Typical materials characterisation techniques were used to analyze the physical and mechanical properties as well as the bioactivity of the as-synthesize and sintered samples. The result confirmed that these doping ions were incorporated within the crystal structure to form B-type carbonated HA. The [nCO32-/nPO43-] molar ratio = 1.00 revealed a smaller particle size, higher surface area and higher CO32-content compared to [nCO32-/nPO43-] molar ratio = 0.67. Mechanical test for [nCO32-/nPO43-] molar ratio = 1.00 samples at sintering temperatures of 750, 800 and 850 ºC showed hardness and tensile strength values in the range of the cancellous bone. In vitro bioactivity revealed a more bone like apatite in the sintered pellets compared to the as-synthesize powders. The sintered multi-doped samples containing Mg2+, Si4+ and Cu2+ showed more apatite formation after day 21 compared to the other samples. The ion release study and pH profile from the sintered samples showed a stable release within the range found in human. The result as a whole shows the potential of both the nanopowders and sintered samples in the biomedical applications.